Studies on Homalomeneae (Araceae) of Borneo XXI: A New Karst Limestone Obligated Homalomena Species Endemic to Niah Caves - BOYCE, PETER C. (Borneo Journal of Resource Science and Technology, 2017)
Homalomena niahensis P.C. Boyce, is described and illustrated as a new species of Homalomena [Homalomena Clade] locally endemic to Niah Caves, Sarawak, Malaysian Borneo, where it is obligated to Karst limestone. Homalomena niahensis is the sixth species to be described for the Homalomena Selaburensis Complex to which its nearest congener is Homalomena selaburensis. An identification key to species of the Homalomena Selaburensis Complex is provided. Keywords: Araceae, Borneo, Homalomena, Malaysia, Sarawak, Karst limestone